Using country of origin to inform targeted tuberculosis screening in asylum seekers: a modelling study of screening data in a German federal state, 2002-2015 - Bozorgmehr, Kayvan; Erdmann, Stella; Wagner, Ulrich; Joggerst, Brigitte; Szecsenyi, Joachim; Razum, Oliver; Stock, Christian (BMC infectious diseases, 2019)
Screening programmes for tuberculosis (TB) among immigrants rarely consider the heterogeneity of risk related to migrants’ country of origin. We assess the performance of a large screening programme in asylum seekers by analysing (i) the difference in yield and numbers needed to screen (NNS) by country and WHO-reported TB burden, (ii) the possible impact of screening thresholds on sensitivity, and (iii) the value of WHO-estimated TB burden to improve the prediction accuracy of screening yield.